2020
DOI: 10.1007/jhep11(2020)009
|View full text |Cite
|
Sign up to set email alerts
|

Soft photon theorems from CFT Ward identites in the flat limit of AdS/CFT

Abstract: S-matrix elements in flat space can be obtained from a large AdS-radius limit of certain CFT correlators. We present a method for constructing CFT operators which create incoming and outgoing scattering states in flat space. This is done by taking the flat limit of bulk operator reconstruction techniques. Using this method, we obtain explicit expressions for incoming and outgoing U(1) gauge fields. Weinberg soft photon theorems then follow from Ward identites of conserved CFT currents. In four bulk dimensions,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 53 publications
(78 reference statements)
2
35
1
Order By: Relevance
“…We provided a plausibility argument at the end of section 3 by including an internal manifold S q+1 and using the results in [62], but it would be desirable to show it directly in AdS (without internal manifolds) and make the whole argument more rigorous. This might shed light on the soft theorem in flat space; see recent discussions in [89].…”
Section: Jhep11(2020)158mentioning
confidence: 89%
“…We provided a plausibility argument at the end of section 3 by including an internal manifold S q+1 and using the results in [62], but it would be desirable to show it directly in AdS (without internal manifolds) and make the whole argument more rigorous. This might shed light on the soft theorem in flat space; see recent discussions in [89].…”
Section: Jhep11(2020)158mentioning
confidence: 89%
“…We find specific corrections of the soft photon mode and gauge parameter that provide a Ward identity equivalent to the classical soft photon theorem up to 1/l 2 corrections. It has recently been demonstrated that conformal Ward identities are equivalent to the Weinberg's soft theorems defined on a flat spacetime patch resulting from the l → ∞ limit on asymptotically AdS spacetimes [30]. Our Ward identity result has a natural interpretation of being defined at "null infinity" on this patch near the center of AdS [30,31], providing the leading 1/l 2 corrections.…”
Section: Jhep08(2021)105mentioning
confidence: 70%
“…In the limit of l → ∞, we can identify an asymptotically flat patch close to the origin of the AdS spacetime [45] that has recently been used to demonstrate the equivalence of the asymptotically flat spacetime large gauge Ward identity with a CFT Ward identity [30].…”
Section: Jhep08(2021)105mentioning
confidence: 99%
“…The goal is to gain insight into the flat spacetime limit of holography by considering the limit where the radius of curvature → ∞ from the Anti-de Sitter side, where the holographic dual is thought to be a well-defined conformal field theory. Some discussion of the viewpoint has appeared in [11,12].…”
Section: Calculationsmentioning
confidence: 99%
“…The goal of the present work is to study these quantities as a limit of asymptotically anti-de Sitter spacetimes where one may gain additional insight via the anti-de Sitter/conformal field theory correspondence. Some initial works in this direction are [11,12]. It has been shown that the BMS algebra generalizes to a Lie algebroid in asymptotically anti-de Sitter spacetime [13,14].…”
Section: Introductionmentioning
confidence: 99%